Estórias da História da Matemática - Ricardo, Sandra; Amaral, Elza; Macedo, Ângela; Correia, Elisete (História da Ciência e Ensino: construindo interfaces, 2019)
Resumo Se perguntassem a um matemático quais as virtudes e os defeitos da Matemática, ouviriam certamente dizer “poupança de esforço” e “satisfação” versus “ansiedade” e “medo”. Neste trabalho vamos contar algumas Estórias da História da Matemática que, em parte, ilustram as três formas de economia em que assenta a Matemática: a ordem, a generalização e a representação concisa. Palavras-chave: Matemática, Estórias, História. Abstract If one asks a mathematician about the virtues and defects of mathematics, the expressions "effort-saving" and "satisfaction" versus "anxiety" and "fear" would certainly appear. In this work, we will tell some Math History Stories, which, in part, illustrate the three forms of economics on which mathematics is based: order, generalization and concise representation. Keywords: Mathematics, Stories, History.